Pengaruh Pemanfaatan Ekstrak Daun Kelor (Moringa Oleifera) sebagai Bahan Aktif Hair Tonic untuk Perawatan Rambut Rontok - Susiladani, Susiladani; Febri Silvia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research is motivated by the many hair problems, one of which is hair loss. For that, there must be an alternative to overcome it, namely by using hair tonic from traditional ingredients such as moringa leaves. The purpose of this study is to analyze and explain the effect of using moringa leaf extract as an active ingredient in hair tonic for hair loss treatment..This study uses a quantitative method, an experimental research type. The population of this study were students of Makeup and Beauty class of 2021. The sampling technique was purposive sampling. The sample category that had hair problems was more than 100 strands per day. The data collection technique used documentation and observation methods. The data analysis technique used SPSS.21 to see the results of the analysis prerequisite test and hypothesis test..The results showed that the average number of hairs lost before use was 118.75 strands per day and after use decreased to 79.25 strands per day. This decrease shows that moringa leaf extract has the potential to reduce hair loss.